Perkembangan dan Konsep Dasar Manajemen Humas dalam Dunia Pendidikan: Tinjauan Historis - Hadi, Abdul (At- Ta'lim : Jurnal Pendidikan, 2018)
This journal discusses the history of development, definition, function, objective and scope of public relations management globally then we are required to understand and glance back the history of the emergence of "Public Relation" which originated from the crisis strikes the workers of the industry that occurred in United States in 1906. The practice of public relations or Public Relations has evolved and continues to grow consciously or not, with the number of institutions and companies are growing, competition is increasingly tight in grabbing the public's attention, many ways done by institutions or companies to expose the program or policies, even the excellence of the institution, its main purpose is tersampaikanya to the public, by empowering Public relations or Public Relations, which in this case public relations that must relate and maintain direct communication with the community. People are certainly more interested in the offer of quality programs that are packaged well and interesting. Moreover, being in the world of information is very fast and open, an institution or company may not just be silent waiting to get public attention. Keywords: Management, Public Relations, History, Scope